Exploration of the Structure–Property Relationship of Polymer‐Based Composites by Monte‐Carlo‐Coupled Viscoelastic Lattice Spring Model. Issue 3 (12th February 2021) - Cui, Zhiwei; Huang, Yongmin
Abstract: A viscoelastic lattice spring model is applied to real polymer blend containing strong interaction, i.e., chemical bond, to investigate the structure–property correlation in combination of Monte Carlo method modified by cavity diffusion and bond length fluctuation algorithms. Impacts of inclusion ratio, chemical bonds, chain length, and interface orientation on the mechanical response along with fracture mode are quantified through simulation of uniaxial tensile test. It is confirmed that introduction of strong interaction and prolongation in chain length induces observable reinforcement in global modulus and ultimate tensile strength, respectively, and the amplification is more significant when the interface is parallel to external load. Abstract : A novel successive simulation method which combines the Monte Carlo method and a lattice spring model is developed to predict mechanical properties of viscoelastic binary blends. While the former concerns structure evolution, the latter concerns the mechanical calculation. Impacts of filler content, loading orientation, chin length, and existence of chemical bond are studied. Loading curves with various characteristics can be obtained.